Local aids councils in North-West: the construction and communication of meaning within the context of ownership and accountability - Schutte, Paul J.; Boessenkool, Jan (Department of Communication Science, University of the Free State, 2006)
Many groups and individuals are working hard to come to grips with the phenomenon of HIV and Aids in all its complicated aspects, whether it is bio-medical, socio-cultural, gender related and/or socio-economic. One outcome is that governments try to structure and organise a counter-attack on a national, regional, district and local level. This organisational structuring is meant to facilitate and co-ordinate the action against H I V and Aids. Together with this organisational structuring go the hope and expectation for a resulting effective organisational culture. It is hoped that with the implementation of an organisational structure an organisational “culture of ownership and accountability” would develop. However, this does not seem to be the case. In this article the authors present this particular case and argue that the (implicitly) presupposed causality between an organisational structure and a culture of ownership did not realise, as there was and still is too much differentiation in the construction, interpretation and communication of crucial concepts and aspects concerning HIV and Aids. The empiric results confirmed this assertion.
Keywords: HIV/AIDS; North-West government; AIDS council system; PCA Working Document